In vitro STING Activation with the cGAMP-STINGΔTM Signaling Complex - He, Yanpu (Bio-Protocol, 2021)

(untitled) (Bio Protoc)
Activating the STING (stimulator of interferon genes) signaling pathway via administration of STING agonist cyclic GMP-AMP (cGAMP) has shown great promise in cancer immunotherapy. While state-of-the-art approaches have predominantly focused on the encapsulation of cGAMP into liposomes or polymersomes for cellular delivery, we discovered that the recombinant STING protein lacking the transmembrane domain (STINGΔTM) could be used as a functional carrier for cGAMP delivery and elicit type I IFN expression in STING-deficient cell lines. Using this approach, we generated anti-tumoral immunity in mouse melanoma and colon cancer models, providing a potential translatable platform for STING agonist-based immunotherapy. Here, we report the detailed in vitro STING activation protocols with cGAMP-STINGΔTM complex to assist researchers in further development of this approach. This protocol can also be easily expanded to other applications related to STING activation, such as control of various types of infections.